A LOOK AT ADVERTISING AND THE HISTORICAL FORMATION OF ADVERTISING IN UZBEKISTAN (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
In recent years, along with unlimited interest in advertising practice in Uzbekistan, there is a growing need to study theoretical aspects of advertising, including psycholinguistic, sociolinguistic, semiotic and linguocultural aspects.